2019
DOI: 10.1080/21691401.2019.1596925
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of saxagliptin against lipopolysaccharide (LPS)-induced inflammation and damage in human dental pulp cells

Abstract: Bacteria play a pivotal role in the pathological initiation and progression of pulpitis. Lipopolysaccharide (LPS) is recognized as a major component of the outer wall of Gram-negative bacteria. Saxagliptin, a potent inhibitor of dipeptidyl peptidase-4 (DPP-4), has been licensed for the treatment of type 2 diabetes. In this study, we aimed to evaluate the protective effects of saxagliptin against LPS-induced intracellular insults in human dental pulp cells (HDPCs). We found that DPP-4 is expressed in HDPCs. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“… 17 After contacting with the dental pulp tissue, it participates in the intracellular signaling cascades via toll-like receptor 4 (TLR4) and the nuclear factor κB (NF-κB) signals pathway, 18 , 19 In addition, inducing the production and secretion of pro-inflammatory cytokines and chemokines, and create inflammation. 20 , 21 Studies have shown that the medullary cavity built-in LPS method is reliable in establishing a rat model to simulate the process of clinical acute pulpitis. 15 Therefore, the early stage of the acute pulpitis after 24 h of modeling was selected as the main observation time point in detecting the changes of pain-related behaviors, pulp histopathological changes, and the P2X7 receptor expression in pulp tissue with all the experimental rats in each group.…”
Section: Discussionmentioning
confidence: 99%
“… 17 After contacting with the dental pulp tissue, it participates in the intracellular signaling cascades via toll-like receptor 4 (TLR4) and the nuclear factor κB (NF-κB) signals pathway, 18 , 19 In addition, inducing the production and secretion of pro-inflammatory cytokines and chemokines, and create inflammation. 20 , 21 Studies have shown that the medullary cavity built-in LPS method is reliable in establishing a rat model to simulate the process of clinical acute pulpitis. 15 Therefore, the early stage of the acute pulpitis after 24 h of modeling was selected as the main observation time point in detecting the changes of pain-related behaviors, pulp histopathological changes, and the P2X7 receptor expression in pulp tissue with all the experimental rats in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment only with miR146a/PEG-PEI downregulates DMP-1 expression [ 109 ]. Saxagliptin (DDP4 inhibitor) reduces oxidative stress, mitochondrial dysfunction, and levels of IL-1β, IL-8 and TNFα [ 110 ]. Mineral trioxide aggregate is used in clinical practice as a root repair material.…”
Section: Resultsmentioning
confidence: 99%
“…LPS, a component of gram-negative bacteria cell wall, is widely used to induce inflammatory responses in the host cells [ 28 , 29 ]. In our research, the treatment of LPS increased the concentrations of proinflammatory cytokines (TNF- α , IL-1 β , and IL-6) in HMEECs.…”
Section: Discussionmentioning
confidence: 99%